2015
DOI: 10.1087/20150403
|View full text |Cite
|
Sign up to set email alerts
|

Journal publishing models in the Czech Republic

Abstract: ABSTRACT. In 2014 we undertook a survey on the shifts in scholarly publishing in connection with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In contrast, prior studies indicate significantly higher OA shares for other countries and for publications in languages other than English. 18 This detail motivates us to split the data into two world regions (the Big Four countries vs. the rest of the world). This same split has earlier been used in a slightly different context by Solomon et al 19 To account for the scientific quality of journals, we use a simplified method.…”
Section: Methods and Datamentioning
confidence: 99%
“…In contrast, prior studies indicate significantly higher OA shares for other countries and for publications in languages other than English. 18 This detail motivates us to split the data into two world regions (the Big Four countries vs. the rest of the world). This same split has earlier been used in a slightly different context by Solomon et al 19 To account for the scientific quality of journals, we use a simplified method.…”
Section: Methods and Datamentioning
confidence: 99%
“…Navas () found that 37% of the OA journals listed in the Spanish Dulcinea service were also in DOAJ. Suchá and Steinerevá () estimated that 51% of 612 Czech scholarly journals were OA. As only 78 of those were registered in DOAJ, that represents a 25% share of all OA Czech journals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the purpose of professional actors should be better framed as the maximization of the (long-run) enterprise value rather than the (near-term) profit [60], with the implication that the care about the end-user and stakeholder need not differ between for-profit and non-profit publishing ventures. Furthermore, although publishers of different natures are prone to relying on distinct revenue sources, some case studies call into question the assertion that OA and traditional subscription-based journals do not share the same business model [61]. Broadly speaking, whatever the target is, non-profit players also need to cover their costs, which is likely to happen for APCs at a level not too different from that which we are experiencing today, unless substantial savings can be achieved in the investment and operational costs [21,22,62].…”
Section: Discussion: the Academic Publishing Business Modelmentioning
confidence: 99%